2001
DOI: 10.1093/emboj/20.11.2835
|View full text |Cite
|
Sign up to set email alerts
|

Heme mediates derepression of Maf recognition element through direct binding to transcription repressor Bach1

Abstract: Heme controls expression of genes involved in the synthesis of globins and heme. The mammalian transcription factor Bach1 functions as a repressor of the Maf recognition element (MARE) by forming antagonizing hetero-oligomers with the small Maf family proteins. We show here that heme binds specifically to Bach1 and regulates its DNA-binding activity. Deletion studies demonstrated that a heme-binding region of Bach1 is confined within its C-terminal region that possesses four dipeptide cysteine-proline (CP) mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
487
4
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 481 publications
(522 citation statements)
references
References 45 publications
(96 reference statements)
15
487
4
16
Order By: Relevance
“…MAREs are found in the regulatory regions of genes involved in heme metabolism, such as oxidative stress response genes, globin genes, heme oxygenase-1 and erythroid-specific ALAS [72,[78][79][80][81]. It has been suggested that the transcription of genes possessing MAREs is regulated via a balance between transcriptional activation and repression [22,80]. Under normal conditions, when expressed with small Maf proteins, Bach1 is located in the nucleus [77].…”
Section: The Transcriptional Repression Activity Of Bach1 Is Negativementioning
confidence: 99%
See 4 more Smart Citations
“…MAREs are found in the regulatory regions of genes involved in heme metabolism, such as oxidative stress response genes, globin genes, heme oxygenase-1 and erythroid-specific ALAS [72,[78][79][80][81]. It has been suggested that the transcription of genes possessing MAREs is regulated via a balance between transcriptional activation and repression [22,80]. Under normal conditions, when expressed with small Maf proteins, Bach1 is located in the nucleus [77].…”
Section: The Transcriptional Repression Activity Of Bach1 Is Negativementioning
confidence: 99%
“…Bach1 has two functional domains: BTB/POZ and bZip, which regulate protein interaction and DNA binding, respectively ( Figure 2) [22,73]. Studies have revealed that Bach1 possesses six HRM (CP) motifs (see Figure 2A and 2B) that are essential for heme-mediated regulation [22,82].…”
Section: The Transcriptional Repression Activity Of Bach1 Is Negativementioning
confidence: 99%
See 3 more Smart Citations